Paying Less Tax : How to Keep More of Your Money for Saving or Investing - Whiteley, John, 1943- (Oxford How To Books, 1999)
For most people tax is a fact of life. This book shows how it is possible to reduce one's tax burden, by taking advantages of allowances, reliefs and exemptions, and by knowing how to avoid the pitfalls and penalties. The reader will learn how timing your transactions can help.
Include Glossary and Index
Keywords: Tax planning